N-Doped rGO-sike carbon prepared from coconut shell: structure and specific capacitance - Khambali, Imam; Priyanto, Budhi; Asih, Retno; Baqiya, Malik Anjelh; Ramli, Muhammad Mahyiddin; Osman, Nurul Huda; Tunmee, Sarayut; Nakajima, Hideki; Triwikantoro; Zainuri, Mochamad; Darminto (Tech Science Press, 2022)
An rGO−like carbon compound has been synthesized from biomass, i.e., old coconut shell, by a carbonization process followed by heating at 400°C for 5 h. The nitrogen doping was achieved by adding the urea (CH4N2O) and stirring at 70°C for 14 h. The morphology and structure of the rGO-like carbon were investigated by electron microscopies and Raman spectroscopy. The presence of C-N functional groups was analyzed by Fourier transform infrared and synchrotron X-ray photoemission spectroscopy, while the particle and the specific capacitance were measured by particle sizer and cyclic voltammetry. The highest specific capacitance of 72.78 F/g is achieved by the sample with 20% urea, having the smallest particles size and the largest surface area. The corresponding sample has shown to be constituted by the appropriate amount of C–N pyrrolic and pyridinic defects.